2018
DOI: 10.1016/j.ram.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Ácaros del género Demodex: ¿parásitos colonizadores de personas sanas o asociados a patología ocular?

Abstract: Demodex folliculorum and Demodex brevis are mites that are responsible for human demodicosis affecting skin and frequently linked to ocular diseasess. The aim of this work was to determine the association between Demodex sp. and eyelid and eyelash diseases and to establish the predisposing factors for acquiring this parasitic disease. Eyelashes from symptomatic and asymptomatic patients (n=72) between 9 and 82 years old were analyzed, where 53% were positive for Demodex sp., of which 66% manifested ocular symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…However, according to the 18S rRNA sequencing results of one study, the detection rate of Demodex in dander samples scraped from the cheeks of adults over 18 years old was 100% [3]. Many factors may affect ocular surface mite infestation, such as age, diabetes mellitus (DM), dry eye disease (DED), and meibomian gland dysfunction (MGD) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, according to the 18S rRNA sequencing results of one study, the detection rate of Demodex in dander samples scraped from the cheeks of adults over 18 years old was 100% [3]. Many factors may affect ocular surface mite infestation, such as age, diabetes mellitus (DM), dry eye disease (DED), and meibomian gland dysfunction (MGD) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the prevention of OS Demodex infestation plays an important role in ocular surface hygiene. It has been found that multitudinous factors may affect OS Demodex infestation, such as age, diabetes mellitus (DM) [11], dry eye disease (DED) [12], and meibomian gland dysfunction (MGD) [13], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Kasetsuwan et al reported the prevalence of ocular demodicosis as 70% over the age of 80 [30]. In other studies, it was reported that infestation was signi cantly higher in patients with blepharitis over the age of 50, those over 60 years of age, and those with ocular disease over the age of 70 [31,10,26]. However, in some studies, no signi cant difference was found between increasing age and the presence of mites [22,32].…”
Section: C)mentioning
confidence: 99%